Analisis Pengaruh Kepemimpinan, Pelatihan, Dan Motivasi Kerja Terhadap Kinerja Karyawan - Grace C. L Rumbiak; Yohanis Rante; Johanis Wanma (Jurnal Manajemen dan Bisnis, 2023)
Analysis of the Influence of Leadership, Training, and Work Motivation on Employee Performance at PT. Bank Papua Abepura Branch it aims to analyze the influence of leadership, training, and work motivation variables simultaneously and partially, as well as analyze which variables have the dominant influence on the performance of employees of PT. Bank Papua Abepura Branch. The population in this study are employees of PT. Bank Papua, Abepura Branch, with a total of 32 employees. The sampling technique in this study used a saturated sample where all members of the population were sampled. The analytical method used in this study is multiple linear regression analysis. The results of the study show that simultaneously the variables of leadership, training, and work motivation have a positive and significant effect on the performance of employees of PT. Bank Papua Abepura Branch. Partially, the leadership variable has a positive and significant effect on the performance of PT. Bank Papua Abepura Branch, while the variables of training and work motivation have no significant effect on the performance of employees of PT. Bank Papua Abepura Branch. Variables that have a dominant influence on the performance of employees of PT. Bank Papua Abepura Branch is a leadership variable.